Hypervitaminosis D Following Overdose in a Patient with SLE - Roy, Kakali; Basu, Surupa; Kundu, Ritabrata; Das, Joydeep (Journal of Nepal Paediatric Society, 2016)
Vitamin D supplementation has come under lime light and is being prescribed randomly. Often physicians prescribe high doses of Vitamin D. Overdosing may be dangerous if not supervised or followed up. We are presenting one child with all features of hypercalcemia due to hypervitaminosis D following overdose. Doctors should be cautious during prescribing high dose of Vitamin D. J Nepal Paediatr Soc 2016;36(2):196-197.